Optimization and Applications of Modern Wireless Networks and Symmetry - Chen, Pingping; Shi, Long; Fang, Yi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Due to the future demands of wireless communications, this book focuses on channel coding, multi-access, network protocol, and the related techniques for IoT/5G. Channel coding is widely used to enhance reliability and spectral efficiency. In particular, low-density parity check (LDPC) codes and polar codes are optimized for next wireless standard. Moreover, advanced network protocol is developed to improve wireless throughput. This invokes a great deal of attention on modern communications.